Distribution of Amyloid Burden Differs between Idiopathic Normal Pressure Hydrocephalus and Alzheimer's Disease. Issue 1 (1st February 2013) - Kondo, M.; Tokuda, T.; Itsukage, M.; Kuriyama, N.; Matsushima, S.; Yamada, K.; Nakanishi, H.; Ishikawa, M.; Nakagawa, M.
This study aimed to elucidate the incidence and distribution of the cortical retention of Pittsburgh compound B (PIB) in patients with idiopathic normal pressure hydrocephalus (iNPH) and clarify the differences from those in patients with Alzheimer's disease (AD). Ten patients with iNPH without any clinical signs indicative of AD were enrolled in this study. Cerebral retention of PIB in positron emission tomography (PET) in iNPH patients was compared with those in seven age-matched AD patients. The CSF levels of β-amyloid 1–42 peptide (Aβ42), which inversely decrease with cerebral amyloid burden, were also measured. Three of the ten patients with iNPH showed increased cortical PIB retention. Although the mean cortical SUV ratios were similar, the distribution of PIB retention differed widely between the patients with iNPH and AD. PIB retention was limited to the high-convexity parasagittal areas in iNPH patients, whereas it spread over the frontal and parietotemporal areas in AD. The coronal images of PIB-PET were more informative than conventional transverse images in evaluating the distribution pattern of cortical PIB retention. Two iNPH patients with higher cortical PIB retention had the lowest levels of CSF Aβ42, indicating that PIB retention in iNPH would not reflect a simple delay in PIB clearance but its binding to existing Aβ amyloid in the brain. Our results indicate that iNPH is one of the diseases exhibiting cortical PIB retention. The characteristic distribution of PIB retention in iNPH could be useful in the differential diagnosis between iNPH and AD.